Effect of different variants of non-invasive ventilation on the course and outcomes in patients with hypoxemic respiratory failure caused by SARS-nCoV-2 ( COVID-19) - Skoryk, Vita; Korsunov, Volodymyr (ScienceRise: Medical Science, 2020)
Hypoxemic respiratory failure (HRF) or acute respiratory distress syndrome is the most common and severe complication in patients with COVID-19, requiring oxygen and ventilation support. Non-invasive ventilation methods (NIV) allow to maintain adequate oxygenation in patients with HRF, but it remains unclear which NIV regimen is more effective for reducing the need for invasive ventilation and improving outcomes. The aim. To compare the effect of different non-invasive lung ventilation strategies, namely CPAP+PSV and CPAP without PSV on the results of intensive care of patients with HRF caused by SARS-nCoV-2 (COVID-19). Materials and methods. A prospective single-center study of 59 patients with severe SARS-nCoV-2 (COVID-19) with HRF was performed. Depending on the type of NIV, patients were divided into two groups: in patients of group 1 (n=46) respiratory support was performed in CPAP mode without PSV, in patients of group 2 (n=13) - CPAP+PSV. All patients underwent clinical blood tests, biochemical studies aimed at assessing the severity of COVID-19, visualization of lung tissue (chest radiography, ultrasound to determine the profile of B and C), monitoring of gas exchange, echocardiography to assess the state of central hemodynamics. Statistical analysis of the results was performed using the program “Statistica 10”. Estimated mean values, standard deviation. The relative risk (RR) of adverse events was assessed. Results. The use of CPAP without PSV improves the results of intensive care of patients with severe coronavirus disease with the development of HRF. Conclusions. CPAP NIV is a promising method of respiratory support in patients with moderate to severe ARDS caused by SARS-nCoV-2 virus (COVID-19), which needs further study